Real-World Experience of the Comparative Effectiveness and Safety of Combination Therapy with Remdesivir and Monoclonal Antibodies versus Remdesivir Alone for Patients with Mild-to-Moderate COVID-19 and Immunosuppression: A Retrospective Single-Center Study in Aichi, Japan - Jun Hirai; Nobuaki Mori; Daisuke Sakanashi; Wataru Ohashi; Yuichi Shibata; Nobuhiro Asai; Hideo Kato; Mao Hagihara; Hiroshige Mikamo (Viruses, 2023)
The coronavirus disease (COVID-19) pandemic continues to threaten global public health. Remdesivir and monoclonal antibodies have shown promise for COVID-19 treatment of patients who are immunocompromised, including those with cancer, transplant recipients, and those with autoimmune disorder. However, the effectiveness and safety of this combination therapy for patients who are immunosuppressed remain unclear. We compared the efficacy and safety of combination therapy and remdesivir monotherapy for patients with mild-to-moderate COVID-19 who were immunosuppressed. Eighty-six patients treated in July 2021–March 2023 were analyzed. The combination therapy group (CTG) showed a statistically significant reduction in viral load compared with the monotherapy group (MTG) (p < 0.01). Patients in the CTG also experienced earlier resolution of fever than those in the MTG (p = 0.02), although this difference was not significant in the multivariate analysis (p = 0.21). Additionally, the CTG had significantly higher discharge rates on days 7, 14, and 28 than the MTG (p < 0.01, p < 0.01, and p = 0.04, respectively). No serious adverse events were observed with combination therapy. These findings suggest that combination therapy may improve the clinical outcomes of immunosuppressed COVID-19 patients by reducing the viral load and hastening recovery. Further studies are required to fully understand the benefits of this combination therapy for immunocompromised COVID-19 patients.